TINDAK PIDANA PERKOSAAN YANG DILAKUKAN OLEH ANAK DALAM KAJIAN PSIKOLOGI KRIMINAL (Studi Putusan Nomor : 05/Pid.Sus-Anak/2016/PN-Lsm) - Sudana Bambang Suganda; Zulfan Z; Zul Akli (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2022)
Rape is a crime that gets enough attention among the public. In particular, those who commit these crimes are minors, who should play like other children. However, they did an act based on excessive curiosity, so that curiosity resulted in the child being entangled in a rape crime case which was committed because of the curiosity factor. So that researchers are interested in conducting further research with the title "Rape Crimes Perpetrated by Children in the Study of Criminal Psychology (Study of Decision Number: 05/Pid.Sus-Anak/2016/Pn-Lsm)". The purpose of this study is to find out and explain the crime of rape committed by children in the study of criminal psychology, to find out and explain the factors that can make children commit rape committed by children in the study of criminal psychology and to find out and explain the efforts that can be made to prevent there is no crime of rape committed by children in the study of criminal psychology. The research method used in this study is an empirical juridical case approach related to the crime of narcotics abuse. The nature of the research is descriptive, data analysis is rape. The research location is in the Lhokseumawe District Court, the sample consists of informants and respondents. Sources of data in this study are primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research that the author did, it is known that: 1) a review of criminal psychology about children as perpetrators of criminal acts of rape, namely psychologically, the ethics and morals of children are now very degenerate and will be dangerous for the next generation, because the influence of psychology plays a major role in children to commit crimes. rape crime. 2) the causes that can make children commit the crime of rape in this criminal psychology study are due to several factors, namely parenting factors, environmental factors and weak faith factors. 3) Efforts that can be made to prevent the occurrence of rape crimes committed by children in this criminal psychology study are, firstly, parents should pay more attention to and guide the child, secondly by supervising their interactions outside the home and thirdly by providing more views on religious knowledge to children. Suggestions from this research are: 1) to the government or the authorities in order to disseminate the dangers of the risk of the crime of rape, so that children also have more understanding so as not to commit a crime, especially the crime of rape. 2) Parents should pay more attention and provide guidance to their children so as not to commit acts that violate the law. 3) The last is that the community must pay more attention to the social environment of children around the community. As well as conducting recitation activities in the community for children so that children avoid negative actions.